2021
DOI: 10.3389/fpsyt.2021.575005
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Burnout Among Frontline Health Professionals in a High-Risk Area During the COVID-19 Outbreak: A Structural Equation Model

Abstract: Background: The outbreak of coronavirus disease 2019 (COVID-19) resulted in a substantial workload and stress for frontline health professionals in high-risk areas. Little research has investigated the mechanism of occupational burnout among the frontline health professionals located in the center of the epidemic in Wuhan, China.Methods: A total of 199 frontline health professionals from Wuhan Jinyintan Hospital completed the cross-sectional survey. Mechanisms of occupational burnout (according to the Maslach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 33 publications
2
19
2
Order By: Relevance
“…The relationship between gender and burnout is also somewhat controversial (Sanfilippo et al, 2017;Low et al, 2019), in our study, the gender variable was not an influencing factor of burnout in multiple linear regression analysis, which is similar to the results of studies developed in China during the COVID-19 outbreak Li et al, 2021). In our study, HCWs who were older showed higher PA, which was similarity to a study conducted among HCWs in China (Huo et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The relationship between gender and burnout is also somewhat controversial (Sanfilippo et al, 2017;Low et al, 2019), in our study, the gender variable was not an influencing factor of burnout in multiple linear regression analysis, which is similar to the results of studies developed in China during the COVID-19 outbreak Li et al, 2021). In our study, HCWs who were older showed higher PA, which was similarity to a study conducted among HCWs in China (Huo et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…In our study, 48.6% of frontline HCWs were suffering from burnout, higher than the figure (36.5%) reported in a previous study conducted among Chinese HCWs during the pandemic (Huo et al, 2021). The prevalence of EE symptom (37.3%) is higher than that (34.2%) reported in another study conducted in Wuhan Jinyintan Hospital (Li et al, 2021).…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Based on the study findings, we suggest a stepwise approach that identifies the predictors of burnout components (EE, DP, and PA), selects the most vulnerable job category based on the identified predictors, and then manages the target job category, preferentially improving predictors that can exert a favorable influence on other job categories. We also suggest that follow-up studies should identify biomarkers and somatization in the workforce responding to infectious diseases by referring to the psychosomatic symptoms of burnout [ 64 ], biomarkers such as salivary cortisol, or biochemical parameters such as HbA1C [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“… 22 Meanwhile, burnout (eg, emotional exhaustion, depersonalisation) was a contributing factor to the higher PTSS score. 118 As workers may misidentify traumatic symptoms (eg, arousal, detachment) as burnout rather than a traumatic response referring to PTSS, 119 it is necessary to distinguish between PTSS and burnout of HCWs. Workplace health programmes and health surveillance for protecting the mental health of HCWs are needed.…”
Section: Discussionmentioning
confidence: 99%